GRAMMATICAL ERROR FOUND IN INDONESIAN-ENGLISH TRANSLATION OF DISPLAY OBJECT LABELS IN TAMAN PINTAR MUSEUM YOGYAKARTA - Rahmawati, Anindia Ayu (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
Some grammatical errors have been found in the English translation of object labels in Taman Pintar Museum. Adapting the ATA's Framework for Standard Error Marking categories, this study only focuses on the analysis of grammatical errors, misspelling, and mispunctuation of the English translation. The study employs a descriptive qualitative method in which content analysis is applied. After analyzing the data which is 10 (ten) object labels displayed at Taman Pintar Museum, there are 109 sentences of which 102 sentences contain grammatical errors and only 7 have no mistakes. The errors are either the misuse or the lack of subject-verb agreement, tense, word order, preposition, article, and pronoun. In terms of ‘Other’ categories, there are some errors in the use of singularity and plurality, active-passive voice, gerund and to infinitive, parallelism, and redundancy. In addition, there are 10 misspellings and 11 mispunctuations found in the Indonesian-English translation. Therefore, it can be concluded that the English translation of the ten object labels in Taman Pintar Museum has a serious problem in producing grammatically correct English translation.Keywords: museum object label translation, grammatical errors, English translation